Estilos e práticas parentais e desenvolvimento socioemocional em pré-escolares - Martins, Emilly Schuch (2021)
Parental relationships act as a context for children's socio-emotional and cognitive development. Therefore, the way parents relate to their children has direct effects on their emotional development, leading to functional or dysfunctional outcomes. In order to investigate the relationship between parenting styles and practices and socioemotional development in preschoolers, two studies were carried out in this dissertation: Theoretical and empirical study. The first study consists of a systematic review of the literature in order to identify and gather evidence on the effects of parenting dimensions on the recognition of emotions in children up to 12 years old with typical development. Systematic searches were carried out in the Scopus, Virtual Health Library (VHL) and PsycINFO (APA) databases and manual searches in the references of the included studies. The selection of articles was carried out on the Rayyan platform by two independent evaluators and a third evaluator convened for cases of non-consensus. The evaluation of the level of quality of the evidence of the studies was made through the tool The Joanna Briggs Institute Prevalence Critical Appraisal Tool. The final sample consisted of eight articles. Most studies have found a significant association between parenting practices such as physical punishment, neglect and abuse and a negative impact on the ability to recognize emotions in children. Whereas positive practices, such as teaching emotions and labeling emotions, are associated with positive development of ability in childhood. It is noteworthy that it is not possible to say that these relations are generalizable due to the size of the effect of the results, which were considered weak, although significant. However, it is observed that different studies, using different methodologies and instruments, were able to indicate the same trend. The second study is an empirical investigation about the relationship between parenting styles and practices and socioemotional development (recognition of emotions, empathy, theory of mind and tolerance to frustration) in preschoolers. It is a quantitative, correlational and cross-sectional study. The sample consisted of 100 guardians of children aged 4 and 5 years. The instruments used were: Sociodemographic questionnaire, Questionnaire of Parenting Styles and Dimensions (QEDP), Scale of Memories about Parenting Practices - Parent version (EMBU-P), Empathy Questionnaire (EmQue), The Perception of Theory of Mind of Children Measured (PCToMM-E). To assess the recognition of emotions and tolerance to frustration, questions designed for this study were used. The results indicated that the predominant parenting style in the sample was Democratic and the most used parenting practice was the Emotional Support. In addition, the socio-demographic variables of income, education level, number of children, respondent (father or mother) and sex of the child had significant effects on the outcomes of parenting. The correlation analyzes showed moderate and significant associations between the variables of parenting and child socio-emotional development. However, when regression analyzes were carried out and sociodemographic variables were included, not all socioemotional development variables remained associated with parenting variables.